Corrigendum: Around -independence. (29th June 2020) - Chiarellotto, Bruno; Lazda, Christopher
Abstract : We correct the proof of the main -independence result of the above-mentioned paper by showing that for any smooth and proper variety over an equicharacteristic local field, there exists a globally defined such variety with the same ( p -adic and -adic) cohomology.